0360 PAP Adherence, Follow-Up, and Telehealth During the COVID-19 Pandemic. (25th May 2022) - Kim, David; Powell, Tyler; Brock, Matthew; Foster, Shannon; Hansen, Shana
Abstract: Introduction: Positive airway pressure (PAP) is the gold standard therapy for OSA. However, patient follow-up and adherence to PAP therapy remains variable. With the onset of the COVID-19 pandemic, many sleep centers shifted towards telemedicine. In order to evaluate the impact of telehealth, we assessed the rates of follow-up and PAP adherence among patients newly diagnosed with OSA prior to and after the onset of the COVID-19 pandemic. Methods: Patients aged 18-75 years enrolled in our military sleep center who met eligibility criteria were divided into a pre-pandemic group and a pandemic group. For the pre-pandemic group, initial and follow-up clinic appointments occurred via face-to-face encounters. For the pandemic group, these clinic appointments occurred via telephone encounters. PAP follow-up was defined as a clinic appointment occurring within 6 months of the initial OSA diagnosis and the onset of PAP therapy. Adequate PAP adherence was defined as usage of the device ≥ 4 hours per night on ≥ 70% of nights during a consecutive 30-day period. Differences among the two groups regarding PAP follow-up, PAP adherence, and demographic data were analyzed. Results: Eligible patients (n=234) were divided into a pre-pandemic group (n=117) and a pandemic group (n=117). Demographic data for the pre-pandemic group vs. pandemic group included the following: mean age 42.2 vs. 40.3 years; 78.6% vs. 88.0% male; 60.7% vs. 76.9% active duty military, mean BMI 30.1 vs. 30.1; mean AHI 28.5/hr vs. 27.7/hr; mean Epworth Sleepiness Scale score 11.7 vs. 12.0; mean Insomnia Severity Index 16.9 vs. 16.8. The rates of PAP follow-up were 59.0% (pre-pandemic group) vs. 41.0% (pandemic group). The rates of adequate PAP adherence were 34.8% (pre-pandemic group) vs. 25.0% (pandemic group). Conclusion: There were higher rates of PAP follow-up and PAP adherence among patients seen via face-to-face encounters occurring prior to the onset of the COVID-19 pandemic. While utilization of telehealth in our center did not result in improved outcomes, there may still be utility in offering telehealth to the sleep patient population. Additional studies are needed to identify effective interventions that can be implemented to improve rates of PAP follow-up and PAP adherence. Support (If Any): There were higher rates of PAP follow-up and PAP adherence among patients seen via face-to-face encounters occurring prior to the onset of the COVID-19 pandemic. While utilization of telehealth in our center did not result in improved outcomes, there may still be utility in offering telehealth to the sleep patient population. Additional studies are needed to identify effective interventions that can be implemented to improve rates of PAP follow-up and PAP adherence.